DEVELOPING PAPAN RODA BACA PINTAR MEDIA FOR EARLY READING OFG RADE 1 STUDENTS AT SDN CILEGON X - Hikmawati; Odin Rosyidin; Rina Yuliana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to develop Papan Roda Baca Pintar media, to reveal the feasibility of Papan Roda Baca Pintar media, and to determine students’ responses after using Papan Roda Baca Pintar media in early reading learning. The research method used was research and development by adapting and modifying the Borg and Gall research model, which consisted of 6 stages: problem analysis, data collection, product design, design validation/expert testing, design revision, and product testing/limited trials. The product was tested on students door to door with the teacher’s permission. The product feasibility was based on assessment results from material experts, linguists, media experts, and students’ response questionnaires. Data were collected through questionnaires, observations, and documentation. The results of research and development showed that after a series of trials, questionnaires, and expert validations, Papan Roda Baca Pintar media was very feasible. Based on the assessment from material experts, the percentage was 94% in the very feasible category, while the percentage from linguists’ assessment was 71% in the feasible category. After that, the result from media experts was 85% in the very feasible category, and lastly, the result from limited trials (response questionnaires) was 95%, which was also in the very good category on the Likert scale. This result was interpreted through the feasibility test and was categorized as very feasible.